Nódulos de Aschoff em átrios de pacientes com cardiopatia reumática crônica - Moyses Pedro Amoury Nader (2015)
OBJECTIVE: To assess the prevalence of rheumatic disease activity in atrial appendage (auricle) of patients with a preoperative diagnosis of chronic disease and its correlation with age and gender; assess whether intra and postoperative complications as well as location of valve involvement would be related to the presence of rheumatic disease activity. METHOD: An observational and prospective study conducted from January 2012 to January 2014 in 72 patients with clinical, laboratory and imaging diagnosis of chronic rheumatic heart disease preoperative. The age ranged between 25 and 77 years (mean 47.24 years), and 40 patients were female and 32 were male. Were included patients with uni- or multi valvar disease, first surgery or reoperation,despite age and gender. During surgery for treatment of valvular heart disease atrial appendages biopsies for research Aschoff bodies were taken. The specimens were obtaining through excision of atrial appendages fragments after pericardiotomy and evaluation of the anatomy of the heart. The samples were stored in formaldehyde and sent for histopathology. RESULTS: Aschoff nodules were diagnosed in seven patients (9.72%). Six (85%) patients had isolated rheumatic mitral disease and one (15%) had mitral and aortic disease. There were four deaths. Three in the re-operations group and one in the first operation group. Nonfatal events as mild bleeding, respiratory tract infection, atrial fibrillation, electrolyte balance disorder, prolonged ventilatory support and renal failure occurred in two patients. CONCLUSIONS: Acute rheumatic disease was detected in approximately 10% of patients with preoperative diagnosis of chronic rheumatic disease, was more frequent in younger individuals, with no difference concerning the gender. The presence of rheumatic disease activity had no influence in the incidence of intra- and postoperative complications, and no relation to first surgery or reoperations, location of valve involvement and the type of operation (valvuloplasty or prosthesis).